2017
DOI: 10.1186/s12875-017-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

From good health to illness with post-infectious fatigue syndrome: a qualitative study of adults’ experiences of the illness trajectory

Abstract: BackgroundMunicipal drinking water contaminated with the parasite Giardia lamblia in Bergen, Norway, in 2004 caused an outbreak of gastrointestinal infection in 2500 people, according to the Norwegian Prescription Database. In the aftermath a minor group subsequently developed post-infectious fatigue syndrome (PIFS). Persons in this minor group had laboratory-confirmed parasites in their stool samples, and their enteritis had been cured by one or more courses of antibiotic treatment. The study’s purpose was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
0
15
0
2
Order By: Relevance
“…The participants experienced a five-phased illness trajectory: prodromal, downward, turning, upward and chronic phase [ 47 ]. Here we present impacting factors during the illness trajectory, organized into external/internal and helpful/unhelpful impacting factors for each phase, as experienced and described by the participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants experienced a five-phased illness trajectory: prodromal, downward, turning, upward and chronic phase [ 47 ]. Here we present impacting factors during the illness trajectory, organized into external/internal and helpful/unhelpful impacting factors for each phase, as experienced and described by the participants.…”
Section: Resultsmentioning
confidence: 99%
“…This scale may assist in monitoring the trajectory. Our previously proposed disability model of PIFS (PIFSDM) [ 47 ], the models of Fennel [ 44 ], Ware [ 45 ], Whitehead [ 46 ] and the proposed model of impacting factors in PIFS (PIFSIM) during a four-year long trajectory, presented here, may be seen as complementary means to understand the evolving condition and facilitate clinical observations and help planning treatment in accordance with the needs of each phase. All models are flexible and take into account the relapsing and remitting nature of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myalgic Encephalomyelitis (ME) also known as Chronic Fatigue Syndrome (CFS) or ME/CFS is a debilitating multisystem disease as concluded by the American Institute of Medicine (IOM) in February 2015 after an extensive review of the literature [ 1 ]. It is characterized by rapid (muscle) fatigability after trivial exertion with an abnormally delayed recovery, pain, neurological complaints and autonomic and immunological dysfunction [ 2 ], often resulting in severe functional limitations [ 3 ] rendering at least 25% of patients house and/or bed bound [ 1 ]. The IOM also concluded that there is no effective treatment for it [ 1 ] and the American Federal Agency for Healthcare Research and Quality, removed its recommendation for CBT and GET in July 2016, after concluding that there is no evidence that these treatments are effective [ 4 ].…”
Section: Introductionmentioning
confidence: 99%